Pengetahuan Dan Pelaksanaan Dokumentasi Perawat Terhadap 3S SDKI, SIKI Dan SLKI - Mandira, Tria Monja; Wulandini S, Putri; Fitria, Puja (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2025)
Background: Nursing care standards are inherently linked to the nursing process, which forms the core responsibility of nurses in delivering patient care. This process includes assessment, diagnosis, planning, implementation, and evaluation. The aim of this study is to assess nurses' knowledge and documentation practices related to the 3S components—SDKI, SLKI, and SIKI—at RS Prof. Dr. Tabrani Pekanbaru. Methods: This study employed a quantitative, descriptive research design using a questionnaire. The population consisted of all 40 nurses working at RS Prof. Dr. Tabrani Pekanbaru, and the entire nursing staff was included as the sample. Results: The findings revealed that only 4 respondents (10%) demonstrated good knowledge of SDKI, SIKI, and SLKI. A majority of 20 respondents (50%) had moderate knowledge, while 16 respondents (40%) showed limited understanding of nursing care based on SDKI, SIKI, and SLKI. Conclusion: Based on these results, it can be concluded that the nursing staff has not yet fully comprehended nursing care using the SDKI, SIKI, and SLKI standards. It is recommended that the institution conduct socialization and simulation activities to improve documentation practices aligned with these standards. This initiative is expected to better prepare nurses for applying these standards in healthcare facilities.